The CD147 Protein Complex Is Involved in Entry of Chikungunya Virus and Related Alphaviruses in Human Cells - De Caluwé, Lien; Coppens, Sandra; Vereecken, Katleen; Daled, Simon; Dhaenens, Maarten; Van Ostade, Xaveer; Deforce, Dieter; Ariën, Kevin K.; Bartholomeeusen, Koen (Frontiers in Microbiology, 2021)
Chikungunya virus (CHIKV) is an arbovirus with a global spread and significant public health impact. It is a positive stranded RNA alphavirus belonging to the Togaviridae family. However, many questions about the replication cycle of CHIKV remain unanswered. The entry process of CHIKV is not completely understood nor are the associated virus-receptor interactions fully identified. Here, we designed an affinity purification mass spectrometry coupled approach that allowed the identification of factors that facilitate entry of CHIKV in human cells. The identified entry factors were further validated using CRISPR/Cas9. In HEK293T cells we identified the CD147 protein complex as an entry factor for CHIKV. We further showed the involvement of the CD147 protein complex in the replication cycle of related alphaviruses. Interestingly, CD147 contains similar protein domains as the previously identified alphavirus entry factor MXRA8.